PKM Desa Atep Oki : Peningkatan Pengetahuan Tentang Cara Identifikasi Dan Upaya Preventif Faktor-Faktor Resiko Stroke Pada Masyarakat Pesisir: Peningkatan Pengetahuan Tentang Cara Identifikasi Dan Upaya Preventif Faktor-Faktor Resiko Stroke Pada Masyarakat Pesisir Desa Atep Oki (Tumou Tou: Jurnal Pengabdian Masyarakat, 2023)
Stroke is a non-communicable disease that causes an emergency in the field of neurology. Atep Oki is a village in the coastal area of Minahasa. The majority of the population is people with productive age who work as fishermen. The main health problem in the area is smoking and drinking alcohol accompanied by an increase in blood pressure. These things are risk factors for stroke. Primary prevention of stroke needs to be carried out by increasing public knowledge about how to identify and prevent stroke risk factors with various methods and approaches. Counseling methods, interactive videos and health leaflets with a community approach are ways that can be done to reduce the rate of morbidity, disability and even mortality due to stroke